Investigating the Burden of Chronic Pain: An Inflammatory and Metabolic Composite. (2nd June 2016) - Sibille, Kimberly T.; Steingrímsdóttir, Ólöf A.; Fillingim, Roger B.; Stubhaug, Audun; Schirmer, Henrik; Chen, Huaihou; McEwen, Bruce S.; Nielsen, Christopher S.
Abstract : Background . Chronic pain is associated with increased morbidity and mortality, predominated by cardiovascular disease and cancer. Investigating related risk factor measures may elucidate the biological burden of chronic pain. Objectives . We hypothesized that chronic pain severity would be positively associated with the risk factor composite. Methods . Data from 12, 982 participants in the 6th Tromsø study were analyzed. Questionnaires included demographics, health behaviors, medical comorbidities, and chronic pain symptoms. The risk factor composite was comprised of body mass index, fibrinogen, C-reactive protein, and triglycerides. Chronic pain severity was characterized by frequency, intensity, time/duration, and total number of pain sites. Results . Individuals with chronic pain had a greater risk factor composite than individuals without chronic pain controlling for covariates and after excluding inflammation-related health conditions (p < 0.001 ). A significant "dose-response" relationship was demonstrated with pain severity (p < 0.001 ). In individuals with chronic pain, the risk factor composite varied by health behavior, exercise, lower levels and smoking, and higher levels. Discussion . The risk factor composite was higher in individuals with chronic pain, greater with increasing pain severity, and influenced by health behaviors. Conclusions . Identification of a biological composite sensitive to pain severity and adaptive/maladaptive behaviors would have significant clinical and research utility.